Path Analysis in Dalbergia sissoo Roxb. - Gera, Mohit; Gera, Neelu; Agarwal, Rashmi (Indian Forester, 1999)
In the integrated structure of the plant, the overall correlation observed between two variables is a function of a series of direct and indirect relationships between different variables. To understand the specific forces in building up the total correlation towards productivity in case of Dalbergia sissoo, Path coefficients analysis was carried out. Fourteen characters were included to find out their direct and indirect effects on field height (i.e. productivity). The analysis revealed that the characters polyphenol, number of branches, pod length and germination per cent had higher direct or indirect effects on field height and could be collectively used as selection criteria for improving productivity in Dalbergia sissoo.